ADMINISTRATIVE PRACTICES AND THEIR IMPACT ON STUDENTS’ ACADEMIC PERFORMANCE: A STUDY OF SUPERVISION, DISCIPLINE, MOTIVATION, AND RECORD-KEEPING IN PUBLIC SECONDARY SCHOOLS IN EDO SOUTH SENATORIAL DISTRICT - EGHOMWANRE , OSASERE DEBORAH; OGBEIDE, Agbons Kennedy (Sokoto Educational Review, 2025)
This study investigated the impact of administrative practices on students' academic performance, specifically focusing on supervision, discipline, motivation, and record-keeping in secondary schools within the Edo South Senatorial District, Nigeria. A descriptive survey design was utilized, targeting a population of 2,502 teachers and principals across 137 public senior secondary schools. From this population, 217 respondents were randomly selected from 21 schools spanning the seven local government areas within the senatorial district. Data were collected using a validated instrument called the Nature of School Administrative Environment Questionnaire (SAEQ) and a structured form that captured students' NECO scores in English, Mathematics, and Civic Education. The reliability of the questionnaire was confirmed using the split-half method, yielding a reliability coefficient of 0.98. Hypotheses were tested using Fisher's Z-transformation on Pearson correlation values. Findings revealed that each administrative variable—supervision (r=0.449), discipline enforcement (r=0.437), teacher motivation (r=0.468), and record-keeping (r=0.433)—had a statistically significant and positive influence on students' academic performance ($p\<0.05$). The study concluded that school-level administrative practices play a critical role in improving learning outcomes and educational accountability. It is recommended that policymakers and school managers strengthen administrative structures through targeted training in supervision, behavioral management, teacher support systems, and proper documentation practices. DOI: https://doie.org/10.10318/SER.2025452799